STUDI BIBLIOMETRIK TERHADAP PERFORMANCE JURNAL STANDARDISASI PERIODE 1999-2016 - Abdul Rahman Saleh; Erni Sumarni; Nihayati Nihayati; Muhamad Bahrudin (Perpustakaan Nasional RI, 2016)
Scientific journal is an important information source for researchers because it contains primary research results. This study aims to investigate the performance of Standardization Journal as one of scientific journals. A total number of 298 articles have been published in 49 editions since its early edition to 2016. The study found that the number of articles are fluctuated between 3 to 10 in each edition. Start from volume number 13 in 2011 with 8 articles are constant. However, the number of articles has been constantly kept at 8 since the 13th edition in 2011. There has been 302 writers from 49 institutions who contributed in the publications. The most productive writer is Ellia Kristiningrum with her 14 papers. Collaborative writing’s value is 0.52. It means that the collaborative work is relatively at the same number with its individual counterpart. Sources of information used for references are mostly books.